Climate Anxiety and Water Insecurity: Psychological Responses to Drought in Vulnerable Communities - Alnaimi, Izzeldeen Abdullah; Jaleel Yamani, Ibrahim Abdul; Alkhatib, Ahed J. (International Journal of Aquatic Research and Environmental Studies, 2026)
Climate anxiety is emerging as a legitimate diagnosis; mostly drought communities are the most impacted as one goes through on-ground realities. Water insecurity may have a drought psychological distress linkage. Vulnerable communities’ perspective argues that social environmental and governance processes compound risk. The article states that long-term water scarcity creates chronic uncertainties, real loss of control, disruption to livelihood, stress on household and reduces coping capacity. The drought can exert heavy mental tolls on rural households, farmers, women, displaced populations, low-income groups, older adults, children and people with disabilities. The drought can heavily damage the mental health of the vulnerable community. The assessment and coping strategies, methodological approaches for assessing the adverse impacts of droughts, and the need for integrated measures is also examined. Responses should promote psychosocial support, resiliency of communities, water governance, early-warning systems, and culturally appropriate communication. Combining water security initiatives with mental health initiatives targeting climate anxiety can enhance resilience and policies in a drought.
Keywords: Climate anxiety; water insecurity; drought; psychological distress; vulnerable communities